INCREASING STUDENTS’ PRONUNCIATION USING ENGLISH PRONUNCIATION IPA APPLICATION THROUGH ANDROID - Suadiyatno, Taufik (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
The aim of this research was to know how English pronunciation IPA Android application is able to increase students’ English pronunciation ability and to know to what extent the English Pronunciation IPA application through android is able to increase students’ English pronunciation. This research was Classroom Action Research (CAR). The processes that were applied in this research were planning, acting, observing and reflecting. The instruments that were used to collect the data were observation sheet, test, and questionnaire. This research was held at MA Malaka, North Lombok with 25 second grade students as the subjects of research. This classroom action research was conducted within one cycle. The initial finding before the researchers began the first cycle showed that students score on pre-test was indicated as low score with average mean score 45,88 that achieved through multiple choice and oral test. Research finding in cycle 1 showed that students’ score on post-test was increased to 88, 56 which means that the students’ score increased 31, 75%. Moreover, based on the result of questionnaire they were able to reach on the points of Interesting, Challenging, Comprehending, Understanding, Enhancing, Intelligent, and Advantages. In the other words, English Pronunciation IPA application through android as the teaching media in action research was able to increase students’ English pronunciation.